2009
DOI: 10.4161/cc.8.6.7934
|View full text |Cite
|
Sign up to set email alerts
|

The role of promoter CpG methylation in the epigenetic control of stem cell related genes during differentiation

Abstract: Differentiation and malignant transformation of stem cells are regulated by epigenetic mechanisms. We analyzed promoter methylation and expression of the stem cell determining genes Brachyury, DPPA5, FGF4, FOXD3, LIN28, NESTIN and ZFP42 depending on the differentiation state in human mesenchymal stem cells (MSC), human embryonal carcinoma cells (ECC) and somatic tumor cells. Differentiation of MSC into osteoblasts and adipocytes was accompanied with a loss of expression of the Brachyury gene and downregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 0 publications
1
44
1
Order By: Relevance
“…This process may alter the biology of MSCs and trigger a series of molecular machineries that offer cells an ability to repress replicative senescence by maintaining localized silencing through many cell divisions, during which epigenetic modifications may be major regulators. In this context, DNA methylation mediated by DNMT1 offers an ideal mechanism as the methylation pattern is established on the newly synthesized DNA strand, and DNMT1 can functionally transmit methylation profile from maternal to daughter DNA strands during DNA replications [44,50,51]. In support of this idea, our result of qRT-PCR also showed that the expression of DNMT1 was maintained at an extent level without significant change during the course of the in vitro expansion for fPMSCs.…”
Section: Discussionsupporting
confidence: 85%
“…This process may alter the biology of MSCs and trigger a series of molecular machineries that offer cells an ability to repress replicative senescence by maintaining localized silencing through many cell divisions, during which epigenetic modifications may be major regulators. In this context, DNA methylation mediated by DNMT1 offers an ideal mechanism as the methylation pattern is established on the newly synthesized DNA strand, and DNMT1 can functionally transmit methylation profile from maternal to daughter DNA strands during DNA replications [44,50,51]. In support of this idea, our result of qRT-PCR also showed that the expression of DNMT1 was maintained at an extent level without significant change during the course of the in vitro expansion for fPMSCs.…”
Section: Discussionsupporting
confidence: 85%
“…55,69 Tissue specific methylation of certain developmental genes has been reported. 70,71 Thus the methylation pattern of blood and brain tissues could be also divergent. 70 It will be interesting to investigate methylation profiles in the brains of BPD patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, during osteoblast differentiation this CpG methylation significantly decreased, resulting in enhanced OC expression (Villagra et al, 2006). Furthermore, Dansranjavin et al (2009) demonstrated that MSC differentiation into osteoblast cells was accompanied by reduced expression of the stemness genes via hypermethylation of their promoters.…”
Section: Epigenetic Mechanisms In Neurogenesis and Osteogenesismentioning
confidence: 99%